PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA TIM (STUDI PADA PT. VICTORY INTERNATIONAL FUTURES CABANG SURABAYA TOWN SQUARE) - ONESTYANOVA, KARISMA (Jurnal Ilmu Manajemen (JIM), 2016)
This study uses the independent variable and the dependent variable. The independent variable is the leadership style (X1) and work motivation (X). And as the dependent variable is the performance of the team (Y). The population in this study were employees of PT. Victory International Futures Branch Surabaya Town Square, amounting to 75 people. Sampling method used in this study is Non-Probability Sampling, sample technique saturated ie all members of the population used as a sample. Measurement scale using a Likert Scale, followed by the classical assumption test and test the validity and reliability test for testing the data. Hypothesis testing using multiple linear regression analysis. Keywords: leadership style, motivation, performance.